MicroRNA-338-3p helps regulate ovarian function by affecting granulosa cell function and early follicular development - Ziwen Xu; Tongwei Zhang; Jingyi Hu; Junya Zhang; Guang Yang; Jiahuan He; Huihui Wang; Ran Jiang; Guidong Yao (BMC, 2023)
Abstract Background Follicular development in mammalian ovaries is a complex and dynamic process, and the interactions and regulatory-feedback loop between the follicular microenvironment, granulosa cells (GCs), and oocytes can affect follicular development and normal ovary functions. Abnormalities in any part of the process may cause abnormal follicular development, resulting in infertility. Hence, exploring the pathogenesis of abnormal follicular development is extremely important for diagnosing and treating infertile women. Methods RNA sequencing was performed with ovarian cortical tissues established in vitro. In situ-hybridization assays were performed to study microRNA-338-3p (miR-338-3p) expressed in GCs and oocytes. In vitro culture models were established with GCs and neonatal mouse ovaries to study the biological effects of miR-338-3p. We also performed in vivo experiments by injecting adeno-associated virus vectors that drive miR-338-3p overexpression into the mouse ovarian bursae. Results Sequencing analysis showed that miR-338-3p was expressed at significantly higher levels in ovarian cortical tissues derived from patients with ovarian insufficiency than in cortical tissues derived from patients with normal ovarian function; miR-338-3p was also significantly highly expressed in the GCs of patients with diminished ovarian reserve (P < 0.05). In situ-hybridization assays revealed that miR-338-3p was expressed in the cytoplasm of GCs and oocytes. Using in vitro culture models of granulosa cells, we found that miR-338-3p overexpression significantly suppressed the proliferation and oestradiol-production capacity of GCs (P < 0.05). In vitro culture models of neonatal mouse ovaries indicated that miR-338-3p overexpression suppressed the early follicular development in mouse ovaries. Further analysis revealed that miR-338-3p might be involved in transforming growth factor β-dependent regulation of granulosa cell proliferation and, thus, early follicular development. Injecting miR-338-3p-overexpression vectors into the mouse ovarian bursae showed that miR-338-3p down-regulated the oocyte mitochondrial membrane potential in mice and disrupted mouse oestrous cycles. Conclusion miR-338-3p can affect early follicular development and normal ovary functions by interfering with the proliferation and oestradiol production of GCs. We systematically elucidated the regulatory effect of miR-338-3p on follicular development and the underlying mechanism, which can inspire new studies on the diagnosis and treatment of diseases associated with follicular development abnormalities.